Hindutva as a factor of unification and confrontation in Indian society - Olga L. Solodkova; Mariia S. Antasheva (RUDN Journal of World History)
While in power, the Bharatiya Janata Party (BJP), under the leadership of Narendra Modi, has been using Hindutva - the ideology of the Hindu nationalism - as the basis of its public policies aimed at deeply modernising the country and mobilising the Indian society. Historical memory management becomes a key tool for strengthening the religious identity, with Hindutva acting not only as a unifying narrative but also as an ideological core. Such policies are aimed at creating a new official version of the historical past, which emphasises the emergence of India as a unique Hindu civilization, which evokes mixed reactions among different sections of the Indian society. The relevance of this topic lies in its impact on the political processes of contemporary India and the socio-cultural transformations brought about by the spread of Hindutva. The authors of the study analyse problems of heightened tensions between Hindus and Muslims, the penetration of Hindutva into popular culture, and the political role of caste relations in shaping electoral strategy. Demonstrating heterogeneity of Hindutva perception in the Indian society, the authors identify the major contradictions of the BJP historical policy and its impact on the outcome of the 2024 Lok Sabha elections. Thus, the authors reveal the mechanisms of historical policy formation in India, its influence on social, religious and political processes, as well as make assessments of the prospects for the development of Indian society in the context of the Hindutva growing influence.